The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1111/trf.13678
|View full text |Cite
|
Sign up to set email alerts
|

Motivations for donating and attitudes toward screening policies in US blood donors with viral infection

Abstract: Most donors give to help those in need, including HIV-positive donors. Our results establish a baseline from which additional studies can be compared focused on alternate ways to reduce noncompliance and improved messaging to ensure that high-risk potential donors understand the reasons for blood donor screening policies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
19
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 41 publications
2
19
0
1
Order By: Relevance
“…Subjects of analysis have included blood donor criteria (namely, the MSM criteria), donor perceptions and motivations, as well as comprehension of the PDQ . Nevertheless, some of our findings are consistent with previous studies, such as limited understanding of the window period, and altruistic motives as the primary motivation for blood donation . Moreover, in accordance with our finding that donors conflate and confuse the safety of one's blood (or health) and risk taking, a qualitative study assessed understanding of the American PDQ in the general population and found that all questions were understood, by MSM and non‐MSM alike, “as asking the same thing: that is, ‘is my blood safe to donate?'…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Subjects of analysis have included blood donor criteria (namely, the MSM criteria), donor perceptions and motivations, as well as comprehension of the PDQ . Nevertheless, some of our findings are consistent with previous studies, such as limited understanding of the window period, and altruistic motives as the primary motivation for blood donation . Moreover, in accordance with our finding that donors conflate and confuse the safety of one's blood (or health) and risk taking, a qualitative study assessed understanding of the American PDQ in the general population and found that all questions were understood, by MSM and non‐MSM alike, “as asking the same thing: that is, ‘is my blood safe to donate?'…”
Section: Discussionsupporting
confidence: 88%
“…To our knowledge, this study is the first to apply a qualitative method to the analysis of social perceptions and motivations of blood donation and within a population of donors found positive for HIV. Nevertheless, some quantitative and semiquantitative studies have been conducted on positive blood donors to explore motivations of blood donations and reasons of risk‐factor nondisclosure . Qualitative research has focused more on target groups such as MSM blood donors, MSM, the general blood donor population, or in the general population .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible explanations for this include that previously excluded MSM that chose to donate had lower HIV risk than MSM in general, or that public health HIV testing was effective in ensuring most were aware of their status. Other reasons could be: deferrals for other eligibility criteria, that these men self‐assess as low risk correctly and self‐defer, or that altruistic, community‐oriented MSM who want to donate are simply a low‐risk group .…”
Section: Discussionmentioning
confidence: 99%
“…donors in steady partnerships), studies showed that a considerable proportion of infected donors is aware of risk behavior and makes use of the free, sensitive, and confidential testing to check infection status. A study among US donors with sexually transmissible viral infections showed 19% test-seeking donors [24]; in France 56% of HIV-infected donors reported test-seeking motivation [25]. In a German case control study, HIV test seeking behavior was significantly more present in HIV-positive donors than in controls [26].…”
Section: Discussionmentioning
confidence: 99%